Monitoring the restore process in a degraded area in the South of Brazil Monitoramento do processo de restauração em uma área degradada no sul do Brasil - Rech C.C.C.* (2017)
© 2017.We aimed to monitor an area under restauration, in the municipality of Pouso Redondo, Southern Brazil. The floristic-structural composition of adults and juveniles components was analyzed by NMDS, by phytosociological estimative and by adult diametric distribution. Both components demonstrated segregation in NMDS, Baccharis semiserrata DC. showed the highest importance value, Casearia sylvestris Sw. presented the highest index of natural regeneration and the adult diametric distribution showed a "j inverted" pattern. We concluded that the study area is found under an ecological succession process and that there are no impeditive factors for the establishment of juveniles individuals, suggesting an elevated resilience.